Heavy Metal Levels in Vegetables and Soil Cultivated with Industrial Wastewater from Different Sites of Chunian and Jamber, District, Kasur - A. Hussain; SM Bukhari; S. Andleeb; K.U. Rehman; I. Maqsood; A. Javid; A. Hussain; W. Ali; N. Khalid; M.J. Iqbal; H. Yasin (Journal of Applied Sciences and Environmental Management, 2020)
In human diet, vegetables play important role to maintain the physiological conditions. Due to anthropogenic activities and pollution, the food items become contaminated. The present study was performed to evaluate the level of heavy metals in the vegetables irrigated with wastewater across Chunian and Jamber, district, Kasur. Level of heavy metals from the study area like Zinc, Lead and chromium in the soil, water and vegetables was compared. The four sites of each city and 10 vegetables e.g. potato, radish, carrot, fenugreek, spinach, tomato, Onion, Turnip, Cauliflower, Pangalo were selected to conduct the experiment. The vegetables were irrigated with industrial wastewater and the concentration of heavy metals was measured by the atomic absorption spectrophotometer (AAS). We concluded that the level of heavy metals was beyond the FAO limits in irrigated water due to industrial waste. In Jamber and Chunian, the level of Zn and Pb was high and beyond the FAO safe limits in the all water sample, the level of Cr was much higher only in the water sample of one site from Jamber. The concentration of zinc was higher in soil samples as compared to lead and chromium. Zn and Pb in vegetables of study area were labeled as priority pollutants but this concentration was within the safe limits set by FAO. However, constant inspection of heavy metals is recommended to avoid accumulation in the food chain and thus avoid human health risks.